The adoption of computerized accounting system (cas) in small and medium scales enterprises(smes): with special reference to smes located in matara district, sri lanka - Darshi, G.A.N.; Nanayakkara, M.S.; Gunawardene, T.S.L.W (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
Computerized Accounting System (CAS) plays prominent role in providing information accurately and quickly to meet challenges of ever-changing business environment.Developing countries, however,struggle and are reluctant towards adopting CAS in SMEs. Sri Lanka as an emerging economy, few studies have attempted to study the reticence of adopting CAS in SME sector.SME sector is vitalin developing economy as it generates employment, promotes the growth of Gross Domestic Product (GDP) and stimulates other economic activities. The study examines thefactors which affect to theadoption of CAS in SMEs in Sri Lanka. According to the literature the various factors were identified and broadly classified underdifferent categories. In this study, four factors are included in the research model as managers’ support, perceived usefulness, ability of bearing the cost and human resource proficiency. This study was conducted through thestructured questionnairesurvey method. Data was collected from118 SMEs representing manufacturing, trading and services sectors in Matara District, Sri Lanka.The study used Partial Least Squares (PLS) path modeling to analyze the collected data. The study results disclosed that manager’s support and firm’s ability of bearing the cost have a positive and statistically significant relationship with adoption of CASin SMEs. As per survey results, it has confirmed that there is a positive relationship between perceived usefulness and HR proficiency on adoption of CAS but it is not statistically significant.
Keywords: Small and Medium Enterprises; Computerized Accounting System; Information Technologyation in the way of processing